Fortellinger Om Integrering I Norske Lokalsamfunn 2021
DOI: 10.18261/9788215042961-2021-02
|View full text |Cite
|
Sign up to set email alerts
|

«Vi er jo et mangfoldssamfunn.» Mangfold som offentlig integreringsfortelling: (re)produksjon av likhet og ulikhet?

Abstract: Sammendrag Kapitlet studerer den offentlige samtalen om integrering, slik den utspiller seg i noen rurale midtnorske lokalsamfunn og regioner gjennom nyhetsoppslag i lokalaviser og intervjuer med ordførere. Et gjennomgående budskap i materialet er at de aktuelle lokalsamfunnene framstilles som stadig mer mangfoldige, noe som tilskrives innvandring, og at en slik utvikling oppleves som ønsket. Kapitlet analyserer hva som ligger i denne selvforståelsen, og hvilke oppfatninger av gode og problematiske forskjeller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
1
3
0
1
Order By: Relevance
“…The findings also link up to an insistence on the part of many integration researchers that integration should be studied in its local context, and not only as a national matter (Hadj Abdou, 2019; Sætermo et al., 2021). The findings in our analysis echo some of the insights from this research, in that in its local settings, integration is typically approached pragmatically and in relation to aims of revitalization and development, as opposed to national narratives in which integration is often presented as ‘a problem to be solved’ (Brekke & Mohn, 2018; Gullikstad & Kristensen, 2021). Local narratives of integration, such as those studied here, make integration a ‘local thing’ by drawing on and reproducing notions of rural place qualities that favour and facilitate integration, in ways that tap into the local population's notions of the place.…”
Section: Narratives Of Refugee Settlement and The Ruralsupporting
confidence: 73%
See 1 more Smart Citation
“…The findings also link up to an insistence on the part of many integration researchers that integration should be studied in its local context, and not only as a national matter (Hadj Abdou, 2019; Sætermo et al., 2021). The findings in our analysis echo some of the insights from this research, in that in its local settings, integration is typically approached pragmatically and in relation to aims of revitalization and development, as opposed to national narratives in which integration is often presented as ‘a problem to be solved’ (Brekke & Mohn, 2018; Gullikstad & Kristensen, 2021). Local narratives of integration, such as those studied here, make integration a ‘local thing’ by drawing on and reproducing notions of rural place qualities that favour and facilitate integration, in ways that tap into the local population's notions of the place.…”
Section: Narratives Of Refugee Settlement and The Ruralsupporting
confidence: 73%
“…Such understandings of rural communities go against common notions of the rural as backward and stagnant and see them as more closely connected with progressive and diverse urban societies (McAreavey & Argent, 2018). Moreover, studies have shown that successful experiences with integration are used as arguments for future settlement policies in rural regions and municipalities, as well as to attract newcomers (Gullikstad & Kristensen, 2021; Kristensen & Gullikstad, 2022; Kristensen & Sætermo, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that rural localities may constitute primary settings of immigrant integration and may overshadow the importance of the national context (De Lima, 2012; Stachowski & Bock, 2021). At the same time, local and national contexts are not disembedded from one another, which is reflected by tailoring of national welfare and integration policies to local conditions (Båtevik et al., 2019) or when local ideals of integration mirror national discourses (Gullikstad & Kristensen, 2021).…”
Section: International Migration In Rural Areas—incorporating the Dif...mentioning
confidence: 99%
“…Imidlertid gir verken politikken eller forskningen noen klare svar på hvordan begrepet skal forstås og defineres. Utydeligheten handler blant annet om at begrepet både kan vise til politiske målsettinger og brukes som et analytisk begrep i samfunnsvitenskapen, samt at det også er et ord som etter hvert er blitt en del av alminnelig dagligtale, ofte uten et presist avklart meningsinnhold (Gullikstad et al, 2021;Rytter, 20219. Denne uklarheten er problematisk i integreringsforskningen, der det ofte kan vaere vage grenseoppganger mellom bruken av begrepet i studier av effekter av gjeldende politikk, og i studier som kritisk utforsker spørsmål knyttet til integrering som ide. Det siste har vaert mye debattert de senere årene.…”
Section: Kritiske Perspektiver På Integreringens Underliggende Ideerunclassified